DIAGNOSIS AND TREATMENT OF URETHRAL STRICTURE - Wistara Widya, A.A. Ngr. Agung; Oka, A.A. Gde; Kawiyana, Ketut Siki; Maliawan, Sri (E-Jurnal Medika Udayana, 2013)
Retention of urine is the lower urinary tract obstruction caused by the inability of squirting urine, so that the urine collected in the bladder exceeds the maximum limit. One reason is due to narrowing of the lumen of the urethra, called urethral stricture. The diagnosis of urethral stricture can we enforce by way of history, physical examination, and investigation. Curative treatment of this disease is surgery, but not as rare as some surgical techniques can lead to high disease recurrence for patients.. Thus the proper and adequate treatment is necessary to avoid the risk of recurrence of urethral stricture disease.
Keywords: retention of urine, urethral stricture, treatment